Seed production of bottle gourd is remunerative - Kalyanrao, Kalyanrao; Aher, Bhushan M.; Singh, Balraj (Indian Horticulture, 2019)
Introduction: The average productivity of vegetable crops is 16 tonnes / ha in India. It is lower than the average productivity in China (18.75 tonnes) and USA (28.56 tonnes). The higher productivity in both China and USA is attributed to more use of hybrid seeds and efficient crop management practices. There are a number of hybrids developed in vegetable crops, particularly in bottle gourd from public sector which have higher potential to give better yield and quality. These hybrids should be popularized for their seed production.